Bilateral Pancarpal Arthrodesis in a German Shepherd Dog - Hossein Kazemi Mehrjerdi; Mohammad Mehdi Dehghan; Azin Tavakoli; Alireza Vajhi; Sara Gachpaz (Iranian Journal of Veterinary Surgery, 2008)
Case Description- A 5-year old male German shepherd weighing 28 kg with the history of falling from the third floor 9 months previous was referred to the Small Animal Hospital. Clinical Findings- In clinical examination roughness and thickness of the skin of the palmar surface of both forelimbs were felt. The animal was using his palmar plane of both forelimbs to walk without any signs of pain during walking or weight-bearing. Diagnostic radiographs revealed old traumatic carpal luxation in both forelimbs. Treatment and Outcome- Bilateral pancarpal arthrodesis was performed on both right and left carpal joints in a staged surgery. Under general anesthesia, the carpal joint was reduced and fixation was done at 10 degree extension. A dynamic compressive plate dorsally attached from the distal end of radius to the carpal joint. Arthrodesis was carried out by cancellous bone auto-grafting. Palmar molded splint was applied to support the internal fixation for nine weeks. Survey radiographs during 12 months follow up revealed successful fusion of inflicted joints. Patient exhibited no clinical signs of pain and could normally bear weight on both forelimbs. Clinical Relevance- Plate applications on the dorsal aspect provide easier approach for panarthrodesis of the carpal joint and use of cancellous grafts and external support after surgery increase healing and stability.